2008
DOI: 10.1159/000116744
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Loss after Amniocentesis in a Series of 5,780 Procedures

Abstract: Objectives: Counseling on prenatal diagnosis requires accurate knowledge of the associated risks, including fetal loss. The objective of our study was to assess this risk of amniocentesis in a single center with several operators. Methods: This retrospective analysis concerns only women with singleton pregnancies who underwent amniocentesis between 14+0 and 23+6 weeks’ gestation. Results: During this 4.5-year period, 5,780 amniocenteses were performed, of which we analyzed 5,319. The rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The goals of genetic US screening are to reduce amniocentesis rates and increase detection of chromosomal abnormalities. The risk of fetal loss after the procedure is 1.4% in our department [22] .…”
Section: Other Anomaliesmentioning
confidence: 66%
“…The goals of genetic US screening are to reduce amniocentesis rates and increase detection of chromosomal abnormalities. The risk of fetal loss after the procedure is 1.4% in our department [22] .…”
Section: Other Anomaliesmentioning
confidence: 66%
“…Since then many retrospective studies [5][6][7][8][9][10][11][12] and metanalyses [13] reported amniocentesis-related fetal loss rate between 0.2% and 0.9%. Recent studies reported significantly smaller risks for fetal loss, namely 0.06% [14] and 0.13% [15].…”
Section: Introductionmentioning
confidence: 99%
“…Diverse causes of variation influence the analyses, impacting the individual risk estimation and the decision to perform further invasive testing (which carries an unintended risk for abortion of approximately 1%) (15,16). To reduce this variation, thereby raising detection rate and reducing false-positive rate, it is critical to tighten control or adjust for influencing factors.…”
Section: Discussionmentioning
confidence: 99%